STRENGTHENING ENVIRONMENTAL CARE CHARACTER THROUGH ORGANIC WASTE MANAGEMENT IN “TEBA MODERN” BASED ON THE TRI HITA KARANA PERSPECTIVE AT SD NEGERI 2 CELUK SUKAWATI - Kadek Yudista Witraguna; Heni Kumalasari; Ni Nyoman Serma Adi; Muhammad Yamin; I Wayan Rudiarta; Gracia Marianne Nafsindha Otta; Peni Betasari; Azra Fauzi; Made Sutajaya (UHN I Gusti Bagus Sugriwa Denpasar, 2026)
The Teba Modern program represents a culturally based approach to organic waste management that integrates Balinese local wisdom with environmental education. This study aims to analyze the implementation of Teba Modern in strengthening students’ environmental care character at SD Negeri 2 Celuk Sukawati from the perspective of Tri Hita Karana. A descriptive qualitative method was employed to explore the implementation process, students’ behavioral changes, and the educational values embedded in the program. The findings indicate that Teba Modern contributes positively to the development of students’ environmental responsibility and daily clean-living habits. The values of Tri Hita Karana—Parahyangan, Pawongan, and Palemahan—are reflected through students’ spiritual awareness, social responsibility, and care for the environment. The program not only supports school cleanliness and sustainable waste management but also strengthens character education aligned with the 7 Habits of Great Indonesian Children and the Eight Graduate Profiles. This study highlights the contribution of local wisdom-based environmental programs in integrating ecological awareness with character education in elementary schools.